Profile of Critical Thinking Skills and Learning Motivation of Students in Biology Learning at SMAN 1 Wirosari: Profile of Critical Thinking Skills and Learning Motivation of Students in Biology Learning at SMAN 1 Wirosari - Permata, Indah; Nugroho, Ary; Hayat, Muhammad (UNIB Press, 2025)
Critical thinking skills are essential for students to face the challenges of the 21st century, particularly in biology education. This study aimed to describe the critical thinking skills and learning motivation of students at SMAN 1 Wirosari. Using a descriptive quantitative approach, the research involved 36 students selected through purposive random sampling from a population of 396. Data were collected using an essay-based test for critical thinking and a questionnaire for learning motivation, which were analyzed using statistical tools. Results showed that most students’ critical thinking skills were categorized as low, with an average score of 66.11%. Among five indicators of critical thinking based on Ennis' framework, all were in the medium category. Similarly, students’ learning motivation was mostly in the medium category, with an average score of 67.94%. The low performance in critical thinking and learning motivation was attributed to limited teaching methods and a lack of real-life contextual learning. To address this, innovative approaches such as eco-gamification with an Education for Sustainable Development (ESD) orientation are recommended to enhance students' engagement, motivation, and critical thinking skills.